I assume
are integers to avoid (ir)rational powers of -1.
If
are both even, or if
, then
![\displaystyle \lim_(n\to-1) (x^m+1)/(x^n+1) = (1+1)/(1+1) = 1](https://img.qammunity.org/2023/formulas/mathematics/college/ujn3jw7g4xqcawti49qkrolgf8s97kdbe3.png)
If
are both odd and
, then we can factorize
![(x^m+1)/(x^n+1) = ((x+1)(x^(m-1) - x^(m-2) + \cdots - x + 1))/((x+1)(x^(n-1)-x^(n-2)+\cdots-x+1))](https://img.qammunity.org/2023/formulas/mathematics/college/3p3r0cd0iuovkuuvar05qdqjb9c7ztv4ce.png)
Note that there are
terms in the numerator and
terms in the denominator.
In the limit, the factors of
cancel and
![\displaystyle \lim_(x\to-1) (x^m+1)/(x^n+1) = \lim_(x\to-1) (x^(m-1) - x^(m-2) + \cdots - x + 1)/(x^(n-1)-x^(n-2)+\cdots-x+1) \\\\ ~~~~~~~~~~~~~~~~~~= (1-(-1)+1-(-1)+\cdots-(-1)+1)/(1-(-1)+1-(-1)+\cdots-(-1)+1) \\\\ ~~~~~~~~~~~~~~~~~~=(1+1+\cdots+1)/(1+1+\cdots+1) = \frac mn](https://img.qammunity.org/2023/formulas/mathematics/college/plbuqbhe6mrusoub0jtisuyjk6hm3lac96.png)
If
is even and
is odd, then we can only factorize the denominator and the discontinuity at
is nonremovable, so
![\displaystyle \lim_(x\to-1)(x^m+1)/(x^n+1) = \lim_(x\to-1) (x^m+1)/((x+1)(x^(n-1)-x^(n-2)+\cdots-x+1)) \\\\ ~~~~~~~~~~~~~~~~~~= \frac2m \lim_(x\to-1) \frac1{x+1}](https://img.qammunity.org/2023/formulas/mathematics/college/n8434e7e9wcxaugrnjw5ykendg9hvg64zc.png)
which does not exist.
If
is odd and
is even, then we can factorize the numerator so that
![\displaystyle \lim_(x\to-1)(x^m+1)/(x^n+1) = \lim_(x\to-1) ((x+1)(x^(m-1)-x^(m-2) +\cdots -x+1))/(x^n+1) \\\\ ~~~~~~~~~~~~~~~~~~= \frac{0m}2 = 0](https://img.qammunity.org/2023/formulas/mathematics/college/3xv51w6177qcb7fwquumiwbswq3v41j306.png)